Analytical System for Simultaneous Operando Measurements of Electrochemical Reaction Rate and Hard X-ray Photoemission Spectroscopy. Issue 5 (3rd May 2021) - Suda, Kohei; Kawamoto, Teppei; Yasuno, Satoshi; Watanabe, Takeshi; Koganezawa, Tomoyuki; Matsumoto, Masashi; Imai, Hideto; Hirosawa, Ichiro; Inukai, Junji
Abstract : We have developed an operando analytical system designed for the simultaneous measurements of the electrochemical reaction rate and the hard X-ray photoemission spectrum. In this system, a solution containing reactants was continuously supplied in a Hagen-Poiseuille flow to a specimen, such as catalyst, under the control of temperature, pressure, concentration, and solution flow rate, so that the electrochemical reaction rate is able to be accurately measured or controlled by electrochemical current generated by the reaction. Two different environments, solution and ultra-high vacuum, were connected with an ultra-thin Au/Six Ny window with a thickness of 20 nm to make the operando hard X-ray photoemission spectroscopy possible during the steady-state electrochemical reaction. In this paper, we report this analytical system in detail.